2021
DOI: 10.5194/acp-21-15351-2021
|View full text |Cite
|
Sign up to set email alerts
|

Controls on surface aerosol particle number concentrations and aerosol-limited cloud regimes over the central Greenland Ice Sheet

Abstract: Abstract. This study presents the first full annual cycle (2019–2020) of ambient surface aerosol particle number concentration measurements (condensation nuclei > 20 nm, N20) collected at Summit Station (Summit), in the centre of the Greenland Ice Sheet (72.58∘ N, −38.45∘ E; 3250 ma.s.l.). The mean surface concentration in 2019 was 129 cm−3, with the 6 h mean ranging between 1 and 1441 cm−3. The highest monthly mean concentrations occurred during the late spring and summer, with the minimum concentrations o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 105 publications
0
18
0
Order By: Relevance
“…T* is homogeneous over both the land and the ocean and this suggests that the abundance of INPs and their efficiency is rather similar throughout the region. The only exception is over the Greenland ice sheet (lower T* values, see Figure 2a) where due to its high altitude and frequently cold temperatures, INPs are expected to be washed out during transport to this area (Stopelli et al., 2015) or relatively INP‐depleted air from the free troposphere (Lacher et al., 2018) descends over the ice sheet (Guy et al., 2021). Consistently, field measurements have shown that INP concentrations are lower over the Greenland ice sheet than elsewhere during the Arctic summertime (Wex et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…T* is homogeneous over both the land and the ocean and this suggests that the abundance of INPs and their efficiency is rather similar throughout the region. The only exception is over the Greenland ice sheet (lower T* values, see Figure 2a) where due to its high altitude and frequently cold temperatures, INPs are expected to be washed out during transport to this area (Stopelli et al., 2015) or relatively INP‐depleted air from the free troposphere (Lacher et al., 2018) descends over the ice sheet (Guy et al., 2021). Consistently, field measurements have shown that INP concentrations are lower over the Greenland ice sheet than elsewhere during the Arctic summertime (Wex et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…3d) shows the extension of northern high pressure directly over the location of Oden at this time, suggesting a possible change in air mass. Figure 4 shows an overview of this case, which was first reported in Guy et al (2021) as an potential example of aerosol-limited dissipation. A well-mixed boundary layer topped with a single cloud layer approximately 200 m in thickness ∼ 1200 m above the surface (∼ 4400 m a.s.l.)…”
Section: Ascosmentioning
confidence: 97%
“…While the effects of aerosols and CCN on cloud properties are a focus of much scientific investigation, outside of some recent studies (Mauritsen et al, 2011;Loewe et al, 2017;Stevens et al, 2018;Guy et al, 2021), little has been done to examine the effect of abnormally low aerosol concentrations on clouds. Mauritsen et al (2011) proposed, through observation, the existence of a tenuous cloud regime in which cloud structure is limited by CCN concentration (which, in lower latitudes, often ranges from 100-1000 cm −3 but has been observed to be as low as 1 cm −3 in the Arctic; e.g., Jung et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…LWP values are more variable after 09:00 UTC, but this is most likely due to higher-level liquid clouds passing overhead (which can also be seen on radar in Fig 4b). See Guy et al (2021) for more analysis of these observations. Radar also shows a cloud whose top is lowering but Figure 5c shows little lowering of cloud top.…”
Section: Smtmentioning
confidence: 99%
“…Figure4shows an overview of this case, which was first reported inGuy et al (2021) as an potential example of aerosollimited dissipation. A well-mixed boundary layer topped with a single cloud layer approximately 200 m in thickness ∼1200 m above the surface (∼4400 m ASL) is observed with a balloon sounding the previous day (2019-07-01 at 23:16 UTC, Fig.4a).…”
mentioning
confidence: 95%